Pendampingan Belajar Menulis Bahasa Arab dan Penguasaan Kosakata Pada Anak di Majlis Al-Hidayah Desa Margaluyu - Putri, Sylmi Fazriyah Edysti; Saleh, Abdurrahman; Munir, Dede Rizal (Yayasan Daarul Huda Kruengmane, 2024)
This Community Service Lecture is realized with a learning assistance program that focuses on assisting learning to write Arabic and vocabulary mastery. This mentoring activity was carried out at the al-hidayah council in Margaluyu village, Kiarapedes sub-district, Purwakarta. The aim of this activity is to assist children to have Arabic language skills, especially in mastering vocabulary and writing skills well. The approach to this research uses qualitative methods, namely research procedures that produce descriptive data or qualitative depictions of Assistance in Learning to Write Arabic and Vocabulary Mastery in Children at Majlis Ta'lim Al-Hidayah. The stages of implementing this activity mentoring program are as follows. At this stage, the servant carries out a survey to the al-Hidayah council of Margaluyu village, introductions and requests for permission to serve the leadership of the council. Assistance in Arabic language learning in this program is assistance in learning to write and mastering mufrodat for children. who recited the Koran at Majlis al-Hidayah. After the implementation of assistance in learning to write Arabic and the children's vocabulary mastery at this assembly increased, this service activity generally ran smoothly because the burning enthusiasm and positive response from the children at Majlis al-Hidayah also made this program run well.